2011
DOI: 10.1539/joh.10-0039-oa
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Hours Worked, Symptoms and Health Resource Utilization among Full‐time Male Japanese Workers

Abstract: Associations between Hours Worked, Symptoms and Health Resource Utilization amongFull-time Male Japanese Workers: Keiko Sato, et al. Department of Epidemiology and Health CareResearch, Graduate School of Medicine and Public Health, Kyoto University-Objectives: To investigate the association between hours worked, symptoms experienced, and health resource utilization. Methods: Data were collected from a nationally representative sample of households in Japan. We studied full-time male workers aged 18-65 yr who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Goto et al also reported that there was no relationship between shiftwork, overtime work, stress, or other work factors, and whether or not employees continued treatment [7]. Sato et al reported that full-time employees who had some symptoms were more likely to visit medical institutions if they did less overtime work, and that they were more likely to take supplements if they did more overtime work [24]. Azami et al reported that among employees with diabetes mellitus, those who did not visit medical institutions had higher HbA1c than those who did visit medical institutions, and that working long hours and having holidays other than Sunday increased the risk of not visiting medical institutions [25].…”
Section: Discussionmentioning
confidence: 99%
“…Goto et al also reported that there was no relationship between shiftwork, overtime work, stress, or other work factors, and whether or not employees continued treatment [7]. Sato et al reported that full-time employees who had some symptoms were more likely to visit medical institutions if they did less overtime work, and that they were more likely to take supplements if they did more overtime work [24]. Azami et al reported that among employees with diabetes mellitus, those who did not visit medical institutions had higher HbA1c than those who did visit medical institutions, and that working long hours and having holidays other than Sunday increased the risk of not visiting medical institutions [25].…”
Section: Discussionmentioning
confidence: 99%
“…Associations between consumers’ use of OTCs and their non-demographic/lifestyle factors have been demonstrated in previous studies (Conn 1991 ; Morales-Suárez-Varela et al 2009 ; Villako et al 2012 ). Associations between consumers’ socioeconomic status and their decisions to use either prescription medications or OTCs have also been indicated (Aoyama et al 2012 ; Nielsen et al 2003 ; Sato et al 2011 ). Although it is possible that some of these factors have a direct or indirect influence on consumers’ choices of information providers and channels, as well as on their information needs and their purchases of OTCs, no study investigating such possibilities has been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Japanese study found that men working long hours (N 250 per month) made about half as many physician visits as those working fewer (100-200) hours per month (Sato et al, 2011). A 2007 Canadian study found similar results indicating a statistically significant inverse association between patients' long work hours (N 45 h per week) and utilization of general practitioner services (Fell et al, 2007).…”
Section: Introductionmentioning
confidence: 94%